Komponen dalam Pembangunan Model Kurikulum Agro Menurut Perspektif Islam - Muhammad Yusuf Marlon Abdullah; Azrulkhakim Suradi; Mariam Abd Majid; Halim Mokhtar; Fakhri Sungit; Mardhiah Yahaya; Suwaibah Affandy; Abdul Haiy Mahmod (USIM Press, 2024)
VOL. 8 NO. 1 Page (142-149)